Adjective complementation : an empirical analysis of adjectives followed by that-clauses - Mindt, Ilka (Studies in corpus linguistics, 2011)
This is the first empirical study to focus on adjectives complemented by that-clauses. The in-depth analysis of more than 50,000 cases taken from the British National Corpus gives comprehensive insights into hitherto neglected relations of lexis and grammar. The result of this corpus-driven study is a novel classification of adjectives based on co-occurrence patterns and corroborated with the help of statistical means. The inductive analysis of corpus data offers new perspectives on and innovative descriptions of well-known phenomena of English grammar, such as extraposition or the resultative.